Neglected tropical diseases outside the tropics. - Francesca F Norman; Ana Pérez de Ayala; José-Antonio; Begoña Monge-Maillo; Pilar Zamarrón; Rogelio López-Vélez (Public Library of Science (PLoS), 2010)
BACKGROUND: The neglected tropical diseases (NTDs) cause significant morbidity and mortality worldwide. Due to the growth in international travel and immigration, NTDs may be diagnosed in countries of the western world, but there has been no specific focus in the literature on imported NTDs. METHODS: Retrospective study of a cohort of immigrants and travelers diagnosed with one of the 13 core NTDs at a Tropical Medicine Referral Unit in Spain during the period April 1989-December 2007. Area of origin or travel was recorded and analyzed. RESULTS: There were 6168 patients (2634 immigrants, 3277 travelers and 257 VFR travelers) in the cohort. NTDs occurred more frequently in immigrants, followed by VFR travelers and then by other travelers (p<0.001 for trend). The main NTDs diagnosed in immigrants were onchocerciasis (n = 240, 9.1%) acquired mainly in sub-Saharan Africa, Chagas disease (n = 95, 3.6%) in immigrants from South America, and ascariasis (n = 86, 3.3%) found mainly in immigrants from sub-Saharan Africa. Most frequent NTDs in travelers were: schistosomiasis (n = 43, 1.3%), onchocerciasis (n = 17, 0.5%) and ascariasis (n = 16, 0.5%), and all were mainly acquired in sub-Saharan Africa. The main NTDs diagnosed in VFR travelers were onchocerciasis (n = 14, 5.4%), and schistosomiasis (n = 2, 0.8%). CONCLUSIONS: The concept of imported NTDs is emerging as these infections acquire a more public profile. Specific issues such as the possibility of non-vectorial transmission outside endemic areas and how some eradication programmes in endemic countries may have an impact even in non-tropical western countries are addressed. Recognising NTDs even outside tropical settings would allow specific prevention and control measures to be implemented and may create unique opportunities for research in future.